SAMPLING STRATEGY FOR SPACE MEAN SPEED SURVEY - Suryo Putranto, Leksmono; Sari, Anita; Ivan Santoso, Bernadus (Jurnal Transportasi, 2012)
In most traffic projects, speed survey is required. If the speed survey uses detector, all data might be obtained. Otherwise a sampling strategy needs to be introduced. To ensure the collection of representative sample of speeds there were several sampling options, e.g. collecting sample every regular interval. In this paper three regular intervals were tested, i.e. 30 seconds, 1 minute and 2 minutes 30 seconds. Travel time data was collected in morning, mid day, and afternoon periods in a two-lanes two-ways underpass in Jakarta. Travel speeds were calculated by dividing light vehicle travel times with the underpass length. Space mean speeds were calculated as a light vehicle travel mean speeds/ 5 minutes. The observation of each light vehicle travel times (to get each light vehicle travel speeds) was conducted for the first 15 minutes of three observation periods. More frequent speed sample collection provides higher accuracy.Keywords: space mean speed, sampling strategy, regular interval sampling